Genetic diversity and demography of two endangered captive pronghorn subspecies from the Sonoran Desert - Klimova, Anastasia; Munguia-Vega, Adrian; Hoffman, Joseph I.; Culver, Melanie (Journal of mammalogy, 2014)
Species that have experienced population reduction provide valuable case studies for understanding genetic responses to demographic change. Pronghorn (Antilocapra americana) were once widespread across the North American plains but were subject to drastic population reductions due to overexploitation and habitat fragmentation during the late 19th and early 20th centuries. A. a. peninsularis and A. a. sonoriensis, 2 pronghorn subspecies that inhabit the southern edge of the species' distribution, are almost extinct and now breed almost exclusively in captivity. We therefore sequenced the complete mitochondrial control region and genotyped 18 microsatellite loci in 109 individuals to evaluate the impact of population bottlenecks, captive breeding, small population sizes, and isolation on the genetic composition of captive populations of these 2 subspecies. We found extremely low levels of genetic diversity in both subspecies. The 2 subspecies showed high and significant genetic differentiation, indicating the absence of historic and recent gene flow despite their geographic proximity within the Sonoran Desert. Historical effective population size estimates for the 2 subspecies were inferred to be similar, whereas the Sonoran pronghorn has a contemporary effective size (Ne) more than twice as high as the Peninsular subspecies. Our findings suggest the need for careful genetic management of both subspecies in order to minimize the further loss of genetic variability. Las especies que han experimentado reducciones poblacionales son ejemplos valiosos para entender la repuesta genética al cambio demográfico. En el pasado el berrendo (Antilocapra americana) tenia una amplia distribución en las praderas norteamericanas, sin embargo su población sufrió una drástica reducción por caza descontrolada y fragmentación de su hábitat durante finales del siglo XIX y comienzos del siglo XX. A. a. peninsularis y A. a. sonoriensis, son 2 subespecies del berrendo que habitan el extremo sur del rango de distribución de la especie; ambas se encuentran al borde de la extinción y sobreviven casi exclusivamente en cautiverio. En este estudio, secuenciamos en su totalidad la región control del ADN mitocondrial y genotipificamos 18 loci microsatélites en 109 individuos con el propósito de evaluar el impacto de cuellos de botella poblacionales, reproducción en cautiverio, tamaños poblacionales pequeños y aislamiento sobre la composición genética de estas dos subespecies. Encontramos niveles bajos de diversidad genética en ambas subespecies, particularmente en el berrendo peninsular. Las 2 subespecies mostraron diferenciación genética alta y significativa, lo que implica ausencia de flujo genético histórico y reciente, a pesar de su cercanía geográfica dentro del Desierto Sonorense. Inferimos que el tamaño poblacional histórico efectivo para ambas subespecies fue similar, mientras que el berrendo sonorense tiene un tamaño efectivo contemporáneo 2 veces mayor que el de la subespecie peninsular. Nuestro estudio sugiere que es necesario realizar un manejo genético cuidadoso en ambas subespecies, para así minimizar la pérdida de variabilidad genética durante la reproducción en cautiverio.